Et melopoetisk greb på Grundtvigsalmen - Wierød, Lea (Grundtvig-Studier, 2017)
A Melopoetic Approach to Grundtvig’s Hymns The church hymns written by N.F.S. Grundtvig are simultaneously poems, theological statements and music, but they have predominantly been the subjects of theological research and, to a lesser extent, literary research. Musicological research has avoided literary critique of the texts of hymns and, as a result, has nearly reduced itself to a theological-literary subdiscipline. Hymn scholarship maintains an underlying logocentricsm, which follows conceptions of the text as the actual hymn and the melody as its subsidiary facilitator. These conceptions are implicit in the use of the genitive in the phrase “Grundtvig’s church hymns.” However, this perspective can be defended neither on the basis of Grundtvig’s own hymnological poetics or through contemporary aesthetic theories about how signification is produced in medially mixed utterances, like the church hymn. In this article the author seeks to question the place of church hymns in hierarchies of word-music by shifting focus from the issue of “to what degree does this particular melody redeem Grundtvig’s text” to “what significance is produced from the merging of words and melody in the hymn during its situational utterance”.